N, N-dimethoxy-aminals as dynamic pH-responsive ligations for oligonucleotides - Mozaffari Majd, Mahdieh (My University, 2025)
Dynamic covalent chemistry harnesses the reversible formation of chemical bonds, offering a powerful strategy for designing stimuli-responsive biomolecular systems. This thesis focuses on the development of a novel pH-sensitive linker- N, N – dimethoxy-2,2-bis (aminomethyl)propane-1,3-diol-and its application in oligonucleotide synthesis. The linker was synthesized through a multi-step procedure and characterized using NMR and ESI-TOF HRMS. As outlined in Scheme 1, two synthetic strategies were used to incorporate it into oligonucleotide: (A) immobilization onto a solid support for terminal modification, and (B) conversion into phosphoramidite building block for intrachain modification, including hairpin-forming sequences. Both approaches produced micromole-scale modified oligonucleotide, and ESI-TOF HRMS confirmed successful incorporation. This study introduces N, N-dimethoxy aminal as a promising base-filling linker for dynamic oligonucleotide systems and expands synthetic toolbox for constructing responsive DNA-based nanomaterials. While the pH-responsiveness of linker was not directly evaluated in this study, its chemical design enables the formation of a dynamic covalent aminal bond, which is expected to undergo reversible cleavage under mildly acidic conditions.
Keywords: Dynamic Covalent Chemistry, pH-responsive linker, Reversible aminal, Base filling-element, Oligonucleotide Synthesis